Pembrolizumab for the treatment of diffuse large B-cell lymphoma. (2nd November 2019) - Sheikh, Semira; Kuruvilla, John
ABSTRACT: Introduction : Pembrolizumab is a novel monoclonal antibody that targets the interaction between programmed cell death protein 1 (PD-1) and its ligand (PD-L1). Pembrolizumab has shown significant clinical efficacy in Hodgkin Lymphoma (HL), but results in non Hodgkin Lymphoma (NHL) are mixed. Some NHL subtypes, which share certain genetic features with HL, such as alterations in chromosome 9p24.1 and expression of PD-L1, have shown promising responses in early phase trials. Areas covered : In this review, we provide an overview of pembrolizumab as a compound, and present the available clinical efficacy and safety data in the treatment of diffuse large B cell lymphomas. Expert opinion : Current early phase data suggest that single agent pembrolizumab in NHL demonstrates both efficacy and a favorable safety profile. However, it is anticipated that future treatment strategies will be biomarker-driven and incorporate pembrolizumab into combination therapies with chemotherapy and/or immunotherapy agents.